Rotational complexity increases cropping system output under poorer growing conditions - Bybee‐Finley, K. Ann; Muller, Katherine; White, Kathryn E.; Cavigelli, Michel A.; Eunjin Han; Schomberg, Harry H; Snapp, Sieglinde S.; Viens, Frederi; Correndo, Adrian A.; Deiss, Leonardo; Fonteyne, Simon; Garcia y Garcia, Axel; et al. (Elsevier, 2024)
Growing multiple crops in rotation can increase the sustainability of agricultural systems and reduce risks from increasingly adverse weather. However, widespread adoption of diverse rotations is limited by economic uncertainty, lack of incentives, and limited information about long-term outcomes. Here, we combined 36,000 yield observations from 20 North American long-term cropping experiments (434 site-years) to assess how greater crop diversity impacts productivity of complete rotations and their component crops under varying growing conditions. Maize and soybean output increased as the number of species and rotation length increased, while results for complete rotations varied by site depending on which crops were present. Diverse rotations reduced rotation-level output at eight sites due to the addition of lower-output crops such as small grains, illustrating trade-offs. Diverse rotations positively impacted rotation-level output under poor growing conditions, which illustrates how diverse cropping systems can reduce the risk of crop loss in a changing climate.